2011
DOI: 10.1002/app.35298
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of full and semi Interpenetrating hydrogel from polyvinyl alcohol and poly (acrylic acid‐co‐hydroxyethylmethacrylate) copolymer: Study of swelling behavior, network parameters, and dye uptake properties

Abstract: Semi and full interpenetrating network (IPN) hydrogels were synthesized by allowing free radical copolymerization of acrylic acid (AA) and hydroxyethyl methacrylate (HEMA) in the matrix of polyvinyl alcohol (PVOH). Accordingly, four different semi IPN hydrogels were prepared with PVOH: copolymer mass ratio of 1 : 1, 1 : 0.75, 1 : 0.5, and 1 : 0.25. These hydrogels were designated as SEMIIPN1, SEMIIPN2, SEMIIPN3, and SEMI-IPN4, respectively. In all of these SEMIIPN, after polymerization PVOH was crosslinked wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Determination of carboxylic groups present in the hydrogels. The total amount of carboxylic groups (C, mass% of hydrogel) present in the hydrogels was determined by a method reported elsewhere [8,9]. Around 0.5 g of hydrogel sample (w) was taken in 25 ml 0.1 M NaOH solution and after mixing under magnetic stirring for 2 h it was titrated with 0.1 M HCl solutions.…”
Section: Characterization Of the Hydrogelsmentioning
confidence: 99%
“…Determination of carboxylic groups present in the hydrogels. The total amount of carboxylic groups (C, mass% of hydrogel) present in the hydrogels was determined by a method reported elsewhere [8,9]. Around 0.5 g of hydrogel sample (w) was taken in 25 ml 0.1 M NaOH solution and after mixing under magnetic stirring for 2 h it was titrated with 0.1 M HCl solutions.…”
Section: Characterization Of the Hydrogelsmentioning
confidence: 99%
“…The strong electrostatic interaction among the functional groups of PEG, clay and the copolymer is evident in the spectra of the composite gel. In the NaMMT filled composite gel (F3.2) the 2889 cm −1 peak of PEG due to its CH 2 stretching 32 shifts to 2919 cm −1 and the 1098 cm −1 peak of PEG corresponding to its COC stretching 38 shifts to 1035 cm −1 . The carbonyl stretching of poly (acrylic acid‐co‐acrylamide)/MBA unit is observed to shift from 1665 39 to 1639 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…The Flory's characteristic ratio, C n was taken from the literature as 6.7 31 and C C bond length 'l' was assumed as 1.54 0 A. 32 M r , the molecular weight of the repeat unit was calculated as the weight average of the repeat unit of PEG and the copolymer.…”
Section: Equilibrium Swelling Diffusion and Network Parametersmentioning
confidence: 99%
“…Mandal and coworkers were studied RB adsorption of IPN hydrogel obtained by copolymerization of acrylic acid and hydroxyethylmethacrylate in PVA matrix. They were found the amount of adsorbed dye by hydrogel at about 0.08-0.12 mg/g at a maximum PVA ratio (0.5 wt.%) it was reported that this value was increased up to about 0.12 mg/g after 250 minutes [41]. As far as we know, although no such modification has been made in the literature, considering similar studies mentioned above, it is thought that the proposed method for preparing hydrogel with inorganic fillers modified with the dip-dry technique could be contributed to the dye removal.…”
Section: Adsorption Kinetics Of Rhbmentioning
confidence: 96%